Phosphanylphosphinidene‐Phosphoranes: A Study on Building and Decomposition of Phosphorus‐Rich Chains with Two Ylidic Moieties. Issue 14 (16th March 2020) - Matern, Eberhard; Anson, Christopher E.; Baum, Elke; Sattler, Ewald; Kovács, Ilona
Abstract : The reactions of t Bu2 P–P=P( t Bu2 )CH2 Li at low temperature with dichlorophosphanes RPCl2 (R = Ph, Me, NEt2, t Bu) lead to "P‐7‐chains" as primary products wherein two ylidic moieties are linked by a CH2 –PR–CH2 unit. However, if R = t Bu the long chain is only a by‐product in addition to t Bu2 P–P=P( t Bu2 )Me. The thermal decomposition of "P‐7‐chains" as monitored by 31 P NMR spectroscopy results in t Bu2 P–CH2 –PR–CH2 –P t Bu2 ("P‐3‐chains") and the phosphanylphosphanylidene t Bu2 P–P which is observed as its cyclic trimer or tetramer. In the reactions of t Bu(Me3 Si)P–P=P( t Bu2 )CH2 Li with RPCl2 the corresponding "P‐7‐chains" and the P4 CH2 ‐rings are formed. The substituent R strongly determines the ratio of chain to ring as well as the thermal stability of the products. The solid‐state structures of one representative of both "P‐7‐chains", and of the oxidized derivative of the P4 CH2 ‐ring with R = t Bu were determined by single‐crystal X‐ray diffraction analysis. Abstract : New neutral "P7 ‐chains" with two ylidic moieties linked by a CH2 –P(R)–CH2 unit have been synthesized. The thermal decomposition was followed by 31 P NMR spectroscopy.